Sacralization of the Urban Footpath, with Special Reference to Pavement Shrines in Chennai City, South India - Sekine, Yasumasa (Temenos, 2006)
With regard to urban footpaths, there are two actors with different interests, the municipal authorities who, in theory, pursue town planning and maintain footpaths for the convenience of pedestrians, and the poor homeless living illegally on footpaths with the constant fear of being forced to leave. There exists a clear difference in stand-point between authorities and pavement dwellers on the use of footpaths: the former has a power to keep the public space free from encroachment but the latter finds the footpaths a space advantageous for living. The discussion focuses on pavement shrines that have become more ubiquitous in Chennai city, South India, since the 1990s and are mostly huilt and maintained by the socially and economically weaker sections of the city population. Footpath shrines may have and represent a power of resistance against authorities in the name of the sacred places they have been erected on, and are thus a weapon of the weak in their tactics for survival in the city. This ethnigraphic example holds an important theoretical connotation in terms of the emergence of a dynamic concept of sacred by suggesting that the edge or boudary of the dominant ideological social space or the boudary between the legal and the illegal in its context embraces a potentiality of producing sacrality, as is suggested by Veikko Anttonen's rethinking of the notion of sacred from the viewpoint of cognitive categorization.